Open reduction versus closed reduction percutaneous pinning for the treatment of song type V lateral humeral condyle fractures in children. A short term report - Fang, Jianwen; Wang, Dahui; Tan, Lujian; Peng, Yunbo; Mo, Yueqiang (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate the efficacy of closed reduction percutaneous pinning (CRPP) in the treatment of Song V lateral humeral condyle fractures in children.MethodsMedical records of pediatric patients who underwent surgical treatment for lateral humeral condyle fractures at our institution from July 2018 to August 2024 were retrospectively reviewed. Inclusion criteria: (1). Age ≤14 years; (2). Time from injury to surgery ≤3 days; (3). Song V lateral humeral condyle fracture. Exclusion criteria: (1). Open fracture or concomitant fractures; (2). Associated neurovascular injury; (3). Pathological fracture or concomitant metabolic diseases; (4). Incomplete clinical or radiological data; (5). History of previous surgery on the ipsilateral elbow. Patients meeting the criteria were divided into two groups based on surgical approach: open reduction (n = 43) and closed reduction (n = 46). Gender, age, affected side, intraoperative blood loss, and operative duration were recorded. Elbow function was assessed using the Mayo Elbow Performance Score (MEPS) at the one-year postoperative follow-up. Overgrowth of the lateral condyle was evaluated on anteroposterior radiographs by the presence of a prominent lateral spur; overgrowth was defined as a final interepicondylar width (IEW)/initial IEW ratio >1.1.ResultsThe mean age in the closed reduction group was 4.87 ± 1.55 years, compared to 4.53 ± 1.57 years in the open reduction group, showing no statistically significant difference (t = 1.0126, P = 0.314). There were also no significant differences between the two groups in terms of gender distribution (χ² = 2.715, P = 0.099) or affected side (left/right) (χ² = 0.01, P = 0.914). The closed reduction group demonstrated significantly less intraoperative blood loss (1.02 ± 0.15 mL vs. 3.77 ± 3.22 mL; U = 240.5, P < 0.001) and shorter operative duration (52.96 ± 19.52 min vs. 91.84 ± 30.16 min; U = 275.0, P < 0.001). At the one-year follow-up, no significant difference was found in MEPS (99.78 ± 1.02 vs. 99.53 ± 1.45; U = 841.0, P = 0.180). Evaluation of lateral condyle overgrowth also showed no significant difference between the groups (χ2 = 2.46, P = 0.12).ConclusionClosed reduction percutaneous pinning fixation for Song V lateral humeral condyle fractures achieves surgical outcomes comparable to open reduction. However, CRPP offers the advantages of minimal scarring and significantly shorter operative time.